SOLID AND HAZARDOUS WASTE MANAGEMENT - Mimi Suliza Muhamad (Penerbit UTHM, 2025)
The textbook "Solid and Hazardous Waste Management" provides fundamental knowledge on managing solid and hazardous waste. It is designed for students pursuing a Bachelor of Civil Engineering Technology (Environment) at UTHM. Chapter 1 present an overview of solid waste management. It introduces students to solid waste, including its types, sources, composition, and properties. Chapter 2 covers an overview of hazardous waste management. This includes an introduction to hazardous waste, its definitions, characteristics, and categories. This chapter also addresses on clinical waste and E-waste. Chapter 3 explores legislation on solid and hazardous waste in Malaysia. This chapter outlines the history of solid waste management in Malaysia, the Malaysia plan and national policy, as well as legislation related to both solid and hazardous waste. Chapter 4 focuses on the concept of waste separation and 3R. The topics include waste separation at the source, the hierarchy of ISWM, reduce, reuse, recycle as well as the recycling of materials found in municipal solid waste. Chapter 5 explains on the generation rates, storage, and collection of waste. It provides an overview of the solid waste management process, including waste generation and collection practices. Chapter 6 discusses the transfer and transport of waste. This chapter addresses the need for transfer stations, types of transfer stations and collection vehicles, along with the transportation of hazardous waste. Chapter 7 presents treatment technologies for solid and hazardous waste. This chapter discusses different methods available for treating the waste. Chapter 8 elucidates on waste disposal strategies of both solid and hazardous waste.